Coming to America - Landis, John, 1951-; Sheffield, David; Blaustein, Barry W.; Murphy, Eddie, 1961-; Hall, Arsenio; Jones, James Earl; Rodgers, Niles; Paramount Home Video (Firm) ([Hollywood, Calif.] : Paramount, 1999)
A pampered African prince comes to America in search of a bride, and discovers more than he expected.
Originally released as a motion picture in 1988.
Features: interactive menus, scene selection and theatrical trailer.
Cinematography, Woody Omens; production design, Richard MacDonald; editors, Malcolm Campbell, George Folsey Jr.; music, Nile Rodgers.
Eddie Murphy, Arsenio Hall, James Earl Jones, John Amos, Madge Sinclair, Shari Headley.
MPAA rating: R.
DVD, Dolby digital surround stereo.
Keywords: Video recordings for hard of hearing people; Feature films; Comedy films